Squamous cell carcinoma of gallbladder: a rare entity - Shaikh, Oseen Hajilal; Verma, Shikhar; Balasubramanian, Gopal; Kumbhar, Uday Shamrao; Bhattarai, Sandeep (International Surgery Journal, 2020)
Adenocarcinoma is the most common variant of gallbladder carcinoma. Adenosquamous carcinoma and pure squamous cell carcinoma are rare variants accounting for only up to 3% of the tumors. Pure squamous cell carcinoma of the gallbladder is reported and its incidence is less than 1%. Usually they present at advanced stage and many of the times these are unresectable. Hence survival in patients with squamous cell carcinoma is less than adenocarcinoma, and carries a bad prognosis. We report a rare case of squamous cell carcinoma gallbladder, which was well differentiated, diagnosed early and resected completely. Postoperatively patient is planned for adjuvant chemotherapy.